Kualitas Hidup Pasien Gagal Ginjal yang Menjalani Hemodialisis dengan Metode Single-use dan Re-use di Rspad Gatot Subroto dan RS Pgi Cikini Jakarta: Quality of Life of Kidney Failure Patients Undergoing Hemodialysis with Single-use and Re-use Methods at Gatot Subroto Army Hospital and Pgi Cikini Hospital Jakarta - Moh. Fuad Almubarok; Lestari Sukmarini (NERS Jurnal Keperawatan, 2016)
Haemodialysis may impact on various aspects of patients, including: their daily activities, social roles and psychological aspects. The application of re-use and single-use methods of haemodialysis could be resulting in different quality of life of haemodialysis patients. This study aimed to explore quality of life of kidney failure patients undergoing haemodialysis with single-use and re-use methods. This descriptive study used cross sectional approach, recruited 70 kidney failure patients undergoing haemodialysis by consecutive sampling technique. Data collecting used KDQOL-SF 36 questionnaires and medical record, analysis used univariat and bivariate: Ttest and chi-square test to determine the relating factors of quality of life. The result revealed that there were 45,7% respondents with single-use method had good quality of life and 34,30% respondents with re-use method had good quality of life. The related factors of quality of life were adequacy (P: 0,001), Hb (P: 0,003), albumin (P: 0,001), blood pressure (P: 0,002), and periode of haemodialysis (P: 0,030). The quality of life among those patients (single-use and re-use method) mostly were poor. It is necessary to evaluate quality of life on these patients regularly and consistently, thus initiate to develop nursing management to increase their quality of life.